The Consensus Tigurinus and the Göppingen eucharistic confession: continuing instabilities in Geneva's relationship with Zurich and the Lutheran world. Issue 1 (2nd January 2016) - Cameron, Euan
Abstract : The Zurich Agreement of 1549 between Calvin and Bullinger (the Consensus Tigurinus ) aspired to bring eucharistic teaching in the churches of Zurich and Geneva into harmony. However, while on a diplomatic mission in 1557 to secure the intercession of political leaders in favour of the Waldensian communities under threat from the king of France, Theodore Beza wrote a eucharistic confession which differed radically from the 1549 text; his hope was to persuade South German Lutherans that the Waldenses were closer to Lutheran eucharistic doctrine than the Germans thought. The fallout from this incident, copiously documented in the reformers' letters, provokes in this study some interesting speculations about the differing priorities of Zurich and Geneva on the issue, 8 years after the Consensus .